PENGARUH CORPORATE SOCIAL RESPONSIBILITY, KEPEMILIKAN MANAJERIAL, DAN OPINI AUDITOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR DI BEI PERIODE 2013-2015 (Media Akuntansi, 2018)
Return the results obtained from the investment returns can be return realization has already happened or return expectations that has not happened yet but is expected to happen in the future. Penelitiaan aims to test between pengarauh corporate social responsibility, ownership, management, and the auditor's opinion partially and simultaneously with stock return as dependent variable. Sempel in penelitiaan are 35 studies listed in Indonesia Stock Exchange 2013-2015 period data used are secondary data comes from IDX 2013-2015 and internet. The sample selection using purposive sampling with criteria for companies listed on the Stock Exchange from 2013 to 2015. The independent variables, we choose the corporate social responsibility, managerial ownership, and the auditor's opinion, while the dependent variable used in this study is the stock return. The analytical method used in this research is multiple linear regression to examine the relationship between the independent variables with the dependent variable. Results of analysis of this study showed that the effect of corporate social responsibility, and managerial ownership, significant influence with a positive sign of the significance of below 0:05. and the auditor's opinion influence significantly the negative direction of the significance under 0:05 on stock returns. Test Results determinant coefficient (R2) shows that stock returns are given by the companies sampled in this study can be explained by the independent variable (CSR, KPM, and OA) amounted to 22.9%, while 77.1% are influenced by other factors diliuar models researched. In the F statistical test showed that the independent variables significantly influence stock return on the level of significance of 0000 is less than 0.05. So we can conclude that the independent variable in the study of CSR, KPM, and OA simultaneously affect the stock return.